You and I : living and learning. Adult education in the community. Program 01 - Newfoundland and Labrador Association for Adult Education (Memorial University of Newfoundland. Educational Television Centre, 1982)
In this episode, Dr. Ted Jackson speaks about adult education in personal skills and knowledge, technical skills, and organizational skills.